An integrated evidence-based targeting strategy for determining combinatorial bioactive ingredients of a compound herbal medicine Qishen Yiqi dripping pills. (12th June 2018) - Zhang, Yiqian; Yu, Jiahui; Zhang, Wen; Wang, Yuewei; He, Yi; Zhou, Shuiping; Fan, Guanwei; Yang, Hua; Zhu, Yan; Li, Ping
Abstract: Ethnopharmacological relevance: Qishen Yiqi is a widely used Chinese herbal medicine formula with "qi invigorating and blood activating" property. Its dripping pill preparation (QSYQ) is a commercial herbal medicine approved by the China Food and Drug Administration (CFDA) in 2003 and is extensively used clinically to treat cardiovascular diseases, such as ischemic heart failure and angina pectoris, as well as for the secondary prevention of myocardial infarction. However, the bioactive ingredients of QSYQ remain unclear. As QSYQ is a compound herbal formula, it is of great importance to elucidate its pharmacologically active ingredients and underlying synergetic effects. Aim of the study: This experimental study was conducted to comprehensively determine the combinatorial bioactive ingredients (CBIs) in QSYQ and to elucidate their potential synergetic effects. The established strategy may shed new light on how to rapidly determine CBIs in complex herbal formulas with holistic properties. Materials and methods: An integrated evidence-based targeting strategy was introduced and validated to determine CBIs in QSYQ. The strategy included the following steps: (1) Chemical ingredients in QSYQ were analyzed via UPLC-Q-TOF/MS in the negative and positive modes and were identified by comparison with standard compounds and previously reported data. Their potential therapeutic activities were predicted based on the ChEMBL database to preliminarily search for candidate bioactive ingredients, and their combination was defined as the CBIs. (2) The CBIs were directly trapped and prepared from QSYQ with a two-dimensional chromatographic separation system, and the remaining part was defined as the rest ingredients (RIs). (3) As animal and cell models, left anterior descending coronary artery ligation (LAD)-induced heart failure in rats and hypoxia-induced cardiac myocyte injury in H9c2 cells were applied to compare the potency of QSYQ, CBIs and RIs. (4) The synergetic effects on cardiac myocyte protection of multiple ingredients in CBIs were examined in this cell model. Results: (1) Forty-three ingredients in QSYQ were identified via UPLC-Q-TOF/MS. Based on evidence-based screening using the ChEMBL database, 24 ingredients were predicted to be bioactive ingredients, and their combination was considered the CBIs. (2) The CBIs and RIs were successfully prepared according to a two-dimensional chromatographic system. The CBIs were directly trapped and knocked out from QSYQ by hydrophilic interaction liquid chromatography coupled with reverse-phase liquid chromatography. The remaining part was used as RIs. (3) The results from pharmacological evaluation revealed that CBIs and QSYQ, but not RIs, significantly prevented myocardium injury; improved the ejection fraction (EF) and fractional shortening (FS); decreased the release of cardiac enzymes, including CK, CK-MB, and LDH; alleviated mitochondrial dysfunction; and protected the cell nucleus number and mitochondrial mass. Furthermore, QSYQ and CBIs possessed similar potency. (4) In hypoxia-stimulated H9c2 cells, CBIs showed far greater potency regarding the protection of cardiac myocyte injury than the individual ingredients in QSYQ, exhibiting obvious synergetic effects. Conclusions: An integrated evidence-based targeting strategy was successfully established and validated to determine CBIs from QSYQ with excellent efficiency. Importantly, the holistic property of QSYQ was retained in the CBIs. Hence, this study may shed new light on how to rapidly reveal combinatorial bioactive ingredients from complex prescriptions and will be greatly helpful in the establishment of an appropriate approach to quality control for herbal medicines. Graphical abstract: fx1